A method for preparing aerogel-modified copper substrate

By improving the mixed preparation process of SiO2 aerogel and copper, combined with forging and rolling treatment, high-strength and high-conductivity copper substrates are prepared, which solves the contradiction between strength and conductivity in the prior art and achieves a comprehensive improvement of material performance.

CN116334436BActive Publication Date: 2025-04-01HONGDA TECH BEIJING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310187954.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-02
Publication Date
2025-04-01
Estimated Expiration
2043-03-02

AI Technical Summary

Technical Problem

The prior art is difficult to maintain its conductive properties while increasing the strength of copper alloy materials, especially when using aerogels as reinforced phases, which often significantly reduce.

Method used

By improving the mixing preparation process of SiO2 aerogel and copper, the aerogel powder is blown into the pure copper liquid with high purity nitrogen or argon, and after thorough mixing, casting and cooling, followed by forging and rolling, a copper substrate with high strength and high conductivity is prepared.

Benefits of technology

It achieves the performance of maintaining the conductivity without reducing while increasing the tensile strength, breaking through the inverted relationship between strength and conductivity in the traditional method, and has a simple process, low cost and high production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116334436B_ABST
    Figure CN116334436B_ABST
Patent Text Reader

Abstract

A method for preparing an aerogel-modified copper substrate belongs to the technical field of metal material preparation. The mass percentage composition of the copper substrate includes 0.2‰-0.1% SiO2 aerogel, 99.9% copper, and the remainder is impurities; the method for preparing the copper substrate includes the following steps: A. Melting a pure copper plate in a medium frequency furnace to obtain pure copper liquid; B. Using a graphite tube, using high-purity nitrogen or argon to blow SiO2 aerogel powder into the bottom of the pure copper liquid; pouring the SiO2 aerogel powder and pure copper liquid mixture into a graphite mold for cooling to obtain an aerogel copper ingot; C1. The aerogel copper ingot is subjected to peeling, forging, and cold rolling processes in sequence to obtain a copper strip substrate. The obtained copper substrate has improved tensile strength while not reducing electrical conductivity, breaking through the inverted relationship between tensile strength and electrical conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material preparation, and particularly relates to a method for preparing an aerogel-modified copper strip substrate. Background Art

[0002] With the rapid development of high-tech in recent years, the demand for copper alloys with excellent comprehensive properties such as strength, electrical conductivity, thermal conductivity and corrosion resistance has been increasing. Traditional copper alloy materials are affected by strengthening mechanisms such as solid solution aging. While improving the mechanical properties of the material, the electrical conductivity will decrease to varying degrees. The greater the strength increase, the greater the decrease in electrical conductivity. Therefore, how to find a material that can significantly improve the strength of the material without reducing the electrical conductivity of the material to the greatest extent has become the starting point of this material design.

[0003] Different from the strengthening mechanism of traditional alloyed copper alloy materials, the second phase reinforced copper-based composite material uses nano, submicron and micron particles with high melting point and high hardness as the strengthening phase of the copper matrix. While improving its room temperature and high temperature mechanical properties, its dispersion strengthening mechanism protects the electrical conductivity of the copper matrix to the greatest extent. The research results show that the copper-based composite material prepared by using nano, submicron and micron high melting point hard reinforcement particles as the dispersion reinforcement phase can form dispersed hard points in the soft and tough copper matrix to improve the strength and toughness of the material, while maintaining the high thermal conductivity of copper itself, and improving the softening temperature and fatigue strength. The effect of foreign added particles on electron scattering is smaller than that of solid solution, and has little effect on the electrical conductivity of copper alloys, thereby achieving the effect of comprehensive improvement of strength, electrical conductivity and softening temperature, which has obvious advantages over other strengthening methods.

[0004] According to domestic and foreign data, the most studied materials are Cu / Al2O3 and Cu / SiC composites, but there are few reports on the application of micron-sized silica aerogel in copper alloy materials. Aerogel materials are a very potential strengthening phase due to their special three-dimensional mesh pore structure, low density, high temperature resistance, corrosion resistance and small thermal expansion coefficient. Adding silica aerogel to copper will greatly reduce its electrical conductivity. The reason is that these strengthening technologies essentially introduce various defects into the material, such as grain refinement introduces more grain boundaries, and processing strengthening introduces a large number of dislocations. These defects will significantly increase the scattering of electrons, thereby reducing the conductivity. All these strengthening methods introduce various defects, thereby increasing the scattering of conduction electrons in these defects, and increasing the resistance of the copper matrix. Therefore, achieving high strength and high conductivity of aerogel-modified copper is a major scientific problem that has long been unsolved.

[0005] In recent years, copper-based composite materials have been used in various fields. It is necessary to develop copper-based silica composite materials with high strength, good electrical conductivity and fatigue strength, strong resistance to high temperature softening, high resistance to stress relaxation, and low cost, so that they can be used in the fields of electronics, power, aerospace, transportation, etc., which is of great significance to improving product quality and equipment service life. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a method for preparing an aerogel-modified copper substrate. By improving the mixed preparation process of SiO2 aerogel and copper, the conductivity of the obtained copper substrate is not reduced while the tensile strength is improved, breaking through the inverted relationship between tensile strength and conductivity.

[0007] The technical solution adopted by the present invention is: a method for preparing an aerogel-modified copper substrate, wherein the mass percentage composition of the copper substrate includes 0.2‰-0.1% SiO2 aerogel, 99.9% copper, and the remainder is impurities;

[0008] The preparation method of the copper substrate comprises the following steps:

[0009] A. Melt the pure copper plate in a medium frequency furnace to obtain pure copper liquid, with the melting temperature ≥1100 ℃;

[0010] B. With the help of a graphite tube, use high-purity nitrogen or argon to blow SiO2 aerogel powder into the bottom of the pure copper liquid; with the help of the stirring effect generated during the blowing of high-purity nitrogen or argon, the SiO2 aerogel powder and the pure copper liquid are fully mixed;

[0011] After the spraying is completed, the mixture of SiO2 aerogel powder and pure copper liquid is left to stand for 0.5-2 hours, and then poured into a graphite mold for cooling to obtain an aerogel copper ingot, with a pouring temperature of ≥1100°C;

[0012] C1. The aerogel copper ingot is subjected to peeling, forging and cold rolling processes in sequence to obtain copper strip substrates of various specifications with a thickness ranging from 0.1 to 1 mm;

[0013] C2. The aerogel copper ingot is processed by peeling, forging and drawing in sequence to obtain copper wires of various specifications with diameters ranging from 0.04 to 3 mm.

[0014] Furthermore, the purity of the pure copper plate is ≥99.99%.

[0015] Furthermore, the SiO2 aerogel powder has a D90≤5 μm.

[0016] Furthermore, the process conditions of the forging process of the aerogel copper ingot are heating temperature 800-850 °C, heat preservation for 60 minutes, initial forging temperature 800-850 °C, and final forging temperature 650 °C.

[0017] Furthermore, the aerogel copper ingot is subjected to upsetting and drawing treatment before the cold rolling process:

[0018] ①Use a press to forge, upset and stretch the aerogel copper ingot to break up the coarse solidified structure. The upsetting deformation is 50%.

[0019] ② Use a press to stretch the aerogel copper after upsetting, with a stretching deformation of 20%. After stretching, one side is reversed 90°, and then the stretching deformation is controlled at 20%.

[0020] Furthermore, the cold rolling process further comprises:

[0021] 1) When the deformation of the blank is controlled at 20% and the thickness reaches 3~5mm, the finish rolling is carried out;

[0022] 2) The number of passes for finishing rolling is 4 to 10.

[0023] Furthermore, the copper strip substrate has a tensile strength of 350 MPa-550 MPa and a conductivity of ≥97% IACS.

[0024] Furthermore, the tensile strength of the copper wire is ≥530 MPa and the electrical conductivity is ≥90% IACS.

[0025] Furthermore, the copper strip substrate and the copper wire microstructure are slender strip-shaped grains formed along the drawing direction.

[0026] The role and amount of the elements contained in the present invention are specifically analyzed as follows:

[0027] Aerogel (Al2O3 / SiO2): It has the effect of improving the strength, hardness and high temperature softening resistance of copper-based composite materials. The second phase strengthening effect of aerogel in the copper matrix can effectively hinder dislocation movement and grain boundary sliding, and can significantly improve the strength of the alloy; on the other hand, the lattice distortion caused by the dispersed aerogel particles is relatively less than that of the solid solution strengthening elements, and the hindrance to electron scattering is weak, which has less damage to the electrical conductivity of the copper alloy.

[0028] The beneficial effects of the technical solution of the present invention are as follows: aerogel powder is sprayed into pure copper solution by argon or nitrogen. In this process, aerogel powder and copper solution are fully in contact, and the sprayed gas also has a stirring effect, so that the aerogel and copper solution can be evenly mixed, and the aerogel in the ingot is evenly distributed. The copper substrate obtained by adding aerogel to pure copper for modification treatment, forging, and rolling has high strength (tensile strength greater than 350 MPa) and high conductivity (conductivity greater than 97% IACS), and as the rolling deformation increases, the tensile strength of aerogel copper increases while the conductivity does not decrease, breaking through the inverted relationship between strength and conductivity; pure copper is modified by aerogel, and the presence of aerogel inhibits interface migration, recrystallization and grain growth, so that a copper strip substrate with higher thermal stability can be obtained; the process for obtaining the substrate of the present invention is simple, low cost, and high production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is an aerogel copper ingot obtained by smelting;

[0030] Figure 2 The copper strip substrate obtained by the present invention;

[0031] Figure 3 The copper wire obtained by the present invention;

[0032] Figure 4 is a microstructure diagram of the present invention;

[0033] Figure 5 This is an IPF picture of the copper strip substrate of the present invention. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] It should be noted that the techniques, methods and devices known to those of ordinary skill in the relevant art may not be discussed in detail, but where appropriate, the techniques, methods and devices should be considered as part of the authorization specification. In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not as limiting. Therefore, other examples of the exemplary embodiments may have different values.

[0036] The present invention provides a method for preparing an aerogel-modified copper substrate, wherein the mass percentage composition of the copper substrate includes 0.2‰-0.1% SiO2 aerogel, 99.9% copper, and the remainder is impurities;

[0037] The preparation method of the copper substrate comprises the following steps:

[0038] A. Melt the pure copper plate in a medium frequency furnace to obtain pure copper liquid, with the melting temperature ≥1100 ℃;

[0039] B. With the help of a graphite tube, use high-purity nitrogen or argon to blow SiO2 aerogel powder into the bottom of the pure copper liquid; with the help of the stirring effect generated during the blowing of high-purity nitrogen or argon, the SiO2 aerogel powder and the pure copper liquid are fully mixed;

[0040] After the spraying is completed, the mixture of SiO2 aerogel powder and pure copper liquid is left to stand for 0.5-2 hours, and then poured into a graphite mold for cooling to obtain an aerogel copper ingot, with a pouring temperature of ≥1100°C;

[0041] C1. The aerogel copper ingot is subjected to peeling, forging and cold rolling processes in sequence to obtain copper strip substrates of various specifications with a thickness ranging from 0.1 to 1 mm;

[0042] C2. The aerogel copper ingot is processed by peeling, forging and drawing in sequence to obtain copper wires of various specifications with diameters ranging from 0.04 to 3 mm.

[0043] The purity of the pure copper plate is ≥99.99%. The D90 of the SiO2 aerogel powder is ≤5 μm.

[0044] The process conditions for the forging process of the aerogel copper ingot are as follows: a heating temperature of 800-850°C, heat preservation for 60 minutes, an initial forging temperature of 800-850°C, and a final forging temperature of 650°C.

[0045] The aerogel copper ingot is subjected to upsetting and drawing treatment before the cold rolling process:

[0046] ①Use a press to forge, upset and stretch the aerogel copper ingot to break up the coarse solidified structure. The upsetting deformation is 50%.

[0047] ② Use a press to stretch the aerogel copper after upsetting, with a stretching deformation of 20%. After stretching, one side is reversed 90°, and then the stretching deformation is controlled at 20%.

[0048] Furthermore, the cold rolling process further comprises:

[0049] 1) When the deformation of the blank is controlled at 20% and the thickness reaches 3~5mm, the finish rolling is carried out;

[0050] 2) The number of passes for finishing rolling is 4 to 10.

[0051] The tensile strength of the copper strip substrate is 350 MPa-550 MPa, and the conductivity is ≥97% IACS. The tensile strength of the copper wire is ≥530 MPa, and the conductivity is ≥90% IACS. The microstructure of the copper strip substrate and the copper wire is elongated grains formed along the drawing direction. The elongated grains formed along the drawing direction, and the grains with this organizational feature are more conducive to the movement of free electrons than equiaxed grains, and can weaken the scattering of free electrons caused by the reduction of grain size, increase of grain boundary interfaces and increase of dislocation density due to rolling deformation. Rolling deformation can form a nano-sized layered structure in the copper plate along the rolling direction, with an average layer thickness of 100 nanometers, forming a strong (111) texture. When electrons migrate in elongated grains, they encounter fewer grain boundaries than equiaxed crystals, so the number of electron scattering is low, which damages the conductivity.

[0052] The advantages of the present invention are described below in conjunction with specific embodiments:

[0053] Copper Strip Substrate Example 1-Example 5

[0054] Preparation method of copper strip substrate Example 1-Example 5: Melt a pure copper plate (purity ≥ 99.99%) in a medium frequency furnace, with a melting temperature ≥ 1100 °C to obtain a certain volume of pure copper liquid. Use a blowing method to use high-purity nitrogen or argon gas to penetrate into the bottom of the copper liquid through a graphite tube, blow micron-sized aerogel powder (D90 ≤ 5 microns) into the bottom of the copper liquid, and under the action of the ejected gas, the aerogel powder is fully in contact with the copper liquid and has a stirring effect. After blowing, let it stand for 0.5 to 2 hours. The copper liquid that is fully mixed with the aerogel powder is poured into a graphite mold for cooling, and the pouring temperature is ≥ 1100 °C. After the copper liquid poured into the graphite mold is fully cooled, it forms an aerogel copper ingot with a diameter of 200 mm, and the aerogel copper ingot is peeled (to remove defects such as shrinkage cavities and pits), and then forged and rolled to obtain a 1 mm copper strip substrate. The aerogel contents of the above-mentioned Examples 1-5 are 0.2‰, 0.4‰, 0.5‰, 0.7‰ and 0.1% respectively.

[0055] The thickness of the copper strip substrate of Examples 1-5 can be made into specifications of 0.11 mm, 0.23 mm, 0.56 mm, 0.6 mm and 1 mm, and their physical properties are as follows:

[0056] The experimental results show that the tensile strength of 1 mm copper plate is 429~437 MPa, the conductivity is 101.6%IACS, and the thermal conductivity is 402~419W▪m -1 ▪K -1 Specific heat 420~414J / kg -1 ▪K-1 ;

[0057] The experimental results show that the tensile strength of 0.60 mm copper plate is 470~476 MPa, the conductivity is 99.7% IACS, and the thermal conductivity is 402~419 W▪m -1 ▪K -1 Specific heat 420~414J / kg -1 ▪K -1 ;

[0058] The experimental results show that the tensile strength of 0.56 mm copper plate is 480-484 MPa, the conductivity is 99.4% IACS, and the thermal conductivity is 402~419 W▪m -1 ▪K -1 Specific heat 420~414J / kg -1 ▪K -1 ;

[0059] The experimental results show that the tensile strength of 0.23 mm copper plate is 470~472 MPa, the conductivity is 97.7%IACS, and the thermal conductivity is 402~419W▪m -1 ▪K -1 Specific heat 420~414 J / kg -1 ▪K -1 ;

[0060] The experimental results show that the tensile strength of 0.11 mm copper plate is 500~550 MPa, the conductivity is 97.57% IACS, and the thermal conductivity is 402~419 W▪m -1 ▪K -1 Specific heat 420~414 J / kg -1 ▪K -1 .

[0061] Copper Strip Substrate Comparative Example 1 After adding 1.0~3.0% SiO2 aerogel in the invention patent CN201811609030 (Comparative Example 1), the tensile strength is less than or equal to 230 MPa, and the conductivity is less than or equal to 95.6 IACS. It is much lower than the tensile strength of 350~550 MPa and the conductivity is greater than 97% IACS of the present invention.

[0062] Copper strip substrate comparative example 2 In the invention patent CN202111383933 (Comparative Example 2), after adding 0.3% Al2O3 / SiO2 aerogel, 0.2% Zn, 0.5% Si, and 10% Ni, the tensile strength is 400 MPa and the conductivity is 95% IACS, which are much lower than the tensile strength of 350~550 MPa of the present invention, and the conductivity is greater than 97% IACS, and the conductivity of CN202111383933 (Comparative Example 2) decreases significantly with the increase of aerogel content, and CN202111383933 (Comparative Example 2) uses a cold isostatic pressing followed by hot pressing and sintering process, which has a long process route, and the use of atomized zinc powder, industrial silicon powder, and electrolytic nickel powder inevitably leads to an increase in the cost of raw materials and processing technology.

[0063] Table 1 Performance statistics of copper strip substrate

[0064]

[0065] As can be seen from the above table, compared with the invention patents CN201811609030 (Comparative Example 1) and CN202111383933 (Comparative Example 2), the present invention adopts a method of adding aerogel by blowing high-purity argon gas into the copper liquid. On the one hand, the copper liquid can be disturbed by blowing, and the aerogel and the copper liquid are mixed very evenly; on the other hand, the invention patent CN201811609030 (Comparative Example 1) uses a mode of mixing and briquetting copper powder and aerogel powder. The aerogel powder is added to the copper powder to increase the melting point of the copper powder. The temperature of the copper liquid during the smelting process is 100 higher than the heating temperature of the copper liquid in which the aerogel is added by blowing. o C or above, the copper ingot obtained in this way has a coarse structure after cooling, and its strength and conductivity are worse than those of the aerogel copper obtained by the blowing method. In the mode of using copper powder and aerogel powder for mixed briquetting in CN202111383933 (Comparative Example 2), a large amount of alloying elements such as electrolytic nickel powder and atomized zinc powder are added, resulting in a significant increase in raw material costs. In addition, the cold isostatic pressing and hot pressing sintering processes are used, and the process route is long, and the manufacturing cost will also increase accordingly.

[0066] Copper Wire Example 1-Example 5

[0067] Preparation method of copper wire embodiment 1-embodiment 5: melt a pure copper plate (purity ≥ 99.99%) in a medium frequency furnace, the melting temperature ≥ 1100 ° C, and obtain a certain volume of pure copper liquid. By blowing, high-purity nitrogen or argon is used to penetrate into the bottom of the copper liquid through a graphite tube, and micron-sized aerogel powder (D90 ≤ 5 microns) is blown into the bottom of the copper liquid. Under the action of the ejected gas, the aerogel powder is fully in contact with the copper liquid and has a stirring effect. After blowing, it is left to stand for 0.5 to 2 hours. The copper liquid that is fully mixed with the aerogel powder is poured into a graphite mold for cooling, and the pouring temperature is ≥ 1100 ° C. After the copper liquid poured into the graphite mold is fully cooled, it forms an aerogel copper ingot with a diameter of 200 mm, and copper wire is made by drawing. The aerogel content of the above embodiments 1-embodiment 5 is 0.2‰, 0.4‰, 0.5‰, 0.7‰, and 0.1%, respectively.

[0068] The diameters of the copper wires of Examples 1-5 can be made into specifications of 3 mm, 0.8 mm, 0.18 mm, 0.05 mm and 0.04 mm, and their physical properties are as follows:

[0069] Through this experimental study, the tensile strength of 3 mm diameter copper wire is ≥420 MPa and the conductivity is greater than 99% IACS;

[0070] Through this experimental study, the tensile strength of the 0.8 mm diameter copper wire is ≥530 MPa and the conductivity is greater than 90% IACS;

[0071] Through this experimental study, the tensile strength of the copper wire with a diameter of 0.18 mm is ≥690 MPa, and the conductivity is greater than 90% IACS;

[0072] Through this experimental study, the tensile strength of 0.05 mm diameter copper wire is ≥705 MPa and the conductivity is greater than 90% IACS;

[0073] Through this experimental study, the tensile strength of the 0.04 mm diameter copper wire is ≥900 MPa and the conductivity is greater than 90% IACS.

[0074] Copper wire comparative example 1 The comparative example to be added is: Sayed Abdollah Hosseini et al. prepared pure copper with a grain size of 180 nanometers using the ARB process, High-strength, high-conductivity ultra-finegrains commercial pure copper produced by ARB process, the article was published in Materials and Design 30 (2009) 2911–2918, the highest tensile strength is 700 MPa, and the resistivity is 0.027nΩ.m (46.7%IACS). It should be explained that the ARB process is complex, has extremely high requirements for equipment, and has not yet been able to achieve large-scale production.

[0075] Copper wire comparative example 2 requires additional comparative example: nanocrystalline Cu–0.5 vol.% Al2O3 copper invented by Baohong Tian et al., which is deformed by cold drawing and has a room temperature strength of 455 MPa. The article was published in: Microstructure and properties at elevated temperature of a nano-Al2O3 particles dispersion-strengthened copper base composite, Materials Science and Engineering A 435–436 (2006) 705–710.

[0076] Copper wire comparative example 3: K. Han, RP Walsh, A. Ishmaku, V. Toplosky, L.Brandao,

[0077] Comparative Example 3: JD Embury et al. published an article titled High strength and high electrical conductivity bulk Cu in Philos. Mag. 2004, 84, 3705. The article used low temperature cold drawn copper wire with an ultimate strength of 560 MPa and a conductivity of 95% IACS.

[0078] Table 2 Performance statistics of copper wire

[0079]

Claims

1. A method for preparing an aerogel-modified copper substrate, characterized in that: The copper substrate comprises SiO2 aerogel 0.2‰-0.1%, 99.9% copper, and the remainder is impurities; The preparation method of the copper substrate comprises the following steps: A. Melt the pure copper plate in a medium frequency furnace to obtain pure copper liquid, with the melting temperature ≥1100 ℃; B. With the help of a graphite tube, use high-purity nitrogen or argon to blow SiO2 aerogel powder into the bottom of the pure copper liquid; with the help of the stirring effect generated during the blowing of high-purity nitrogen or argon, the SiO2 aerogel powder and the pure copper liquid are fully mixed; After the spraying is completed, the mixture of SiO2 aerogel powder and pure copper liquid is left to stand for 0.5-2 hours, and then poured into a graphite mold for cooling to obtain an aerogel copper ingot, with a pouring temperature of ≥1100°C; C1. The aerogel copper ingot is subjected to peeling, forging and cold rolling processes in sequence to obtain copper strip substrates of various specifications with a thickness ranging from 0.1 to 1 mm; C2. The aerogel copper ingot is subjected to peeling, forging and drawing processes in order to obtain copper wires of various specifications with a diameter in the range of 0.04-3mm; The copper strip substrate has a tensile strength of 350 MPa-550 MPa and a conductivity of ≥97% IACS; The tensile strength of the copper wire is ≥530MPa and the electrical conductivity is ≥90% IACS.

2. The method for preparing an aerogel-modified copper substrate according to claim 1, characterized in that: The purity of the pure copper plate is ≥99.99%.

3. The method for preparing an aerogel-modified copper substrate according to claim 1, characterized in that: The SiO2 aerogel powder has a D90≤5 μm.

4. The method for preparing an aerogel-modified copper substrate according to claim 1, characterized in that: The process conditions for the forging process of the aerogel copper ingot are as follows: a heating temperature of 800-850°C, heat preservation for 60 minutes, an initial forging temperature of 800-850°C, and a final forging temperature of 650°C.

5. The method for preparing an aerogel-modified copper substrate according to claim 1, characterized in that The aerogel copper ingot is subjected to upsetting and drawing treatment before the cold rolling process: ①Use a press to forge, upset and stretch the aerogel copper ingot to break up the coarse solidified structure. The upsetting deformation is 50%. ② Use a press to stretch the aerogel copper after upsetting, with a stretching deformation of 20%. After stretching, one side is reversed 90°, and then the stretching deformation is controlled at 20%.

6. The method for preparing an aerogel-modified copper substrate according to claim 1, characterized in that The cold rolling process also includes: 1) When the deformation of the blank is controlled at 20% and the thickness reaches 3~5mm, the finish rolling is carried out; 2) The number of passes for finishing rolling is 4 to 10.

7. The method for preparing an aerogel-modified copper substrate according to claim 1, characterized in that: The copper strip substrate and the copper wire microstructure are slender strip-shaped grains formed along the drawing direction.

Citation Information

Patent Citations

  • A silica aerogel-reinforced copper-based composite material and its preparation method

    CN111378863B

  • Copper-based aerogel reinforced copper-based composite material and preparation method thereof

    CN114107729A

  • Aerogel-metal composite material, and preparation method and application thereof

    CN106544539A